Understanding Autism Spectrum Disorder in Context: a comparison of family perceptions in a high income and low/middle-income country - Viljoen, Marisa (Department of Psychiatry and Mental Health, 2019)
Background Autism Spectrum Disorder (ASD) affects individuals from all continents, cultures and socio-economic backgrounds. It presents differently in different individuals and functional outcomes can be highly variable dueto the heterogenous nature of ASD. The context or environment in which individuals live interacts with the core characteristics of ASD to determine functional ability or disability. For this reason the World Health Organization International Classification of Functioning, Disability and Health (ICF) includes environmental factors when measuring and describing functioning. ICF core sets for ASD were recently developed, and included a qualitative study with perspectives from five highly divergent countries (Canada, Sweden, India, Saudi Arabia and South Africa). It is, however, not known whether functional themes in these diverse environments were similar or different. We hypothesized that environmental factors would predominate in low-resource settings where they would be perceived as barriers to functioning. Objectives The purpose of this study was therefore to examine the association between context and functional ability/disability in children with ASD. We aimed firstly, to understand the global landscape of parental perceptions of functioningin their children with ASD. Secondly, we set out to compare and contrast parental perceptions of functioning in two of the most divergent countries that participated in the ICF core set development study. We were interested in the frequency of functional items reported by parents/caregivers from a high- income country and a low/middle income country. We were also interested in the content of the functional items reported by parents/caregivers in these two countries. We selected Sweden as example of a high-income country (HIC), and South Africa, as example of a low/middle-income country (LMIC). Methods To meet the first aim, we performed a scoping review. Two researchers conducted a comprehensive search of peer reviewed studies published between 1990 and June 2016. Full-text of all included articles were accessed and summarized using thematic analysis. Key findings relating to the scoping review question were linked to ICF-CY first or second-level categories. To meet the second aim, we performed secondary analysis of qualitative data from the ICF ASD core set study. Using frequency and content analysis we compared South African (n=22) and Swedish (n=13) participants. The identified ICF-CY categories were ranked and compared for similarities and dissimilarities in frequency of reporting and analyzed for similarities and dissimilarities in the content of themes. Results Thirty three studies were included in the scoping review, and most were conducted in HIC (n = 25/33, 76%) with only six studies in LMIC (n = 6/33, 18%). Two studies compared perspectives from LMIC and HIC (n = 2/33, 6%). Functional themes from HIC included a range across the ICF bio- psychosocial framework with body functions, activities & participation, environmental factors and personal factors all represented. Functional themes from LMIC were predominantly focused on environmental and personal factors. We did, however, acknowledge that different methodologies may have biased findings in HIC versus LMIC. Secondary analysis of the ICF ASD Core set qualitative study therefore used data collected in identical manner in South Africa and Sweden. Complete frequency agreement was seen in 4 ICF categories in thetwo countries - three activities & participation categories (carrying out daily routines, dressing, complex interpersonal interactions), and one environmental factor (immediate family). Obvious differences in frequency of reporting were observed in one environmental factors category (health professionals), six body functions categories (e.g. involuntary movement functions, gait patterns, basic cognitive functions, and mental functions of language), and three activities & participation categories (managing one’s own behaviour, speaking, and undertaking a single task). Only three ICF categories (immediate family, attention functions, products and technology for personal use in daily living) differed in content between South Africa and Sweden. Two additional categories were identified namely health professionals and sensory processing.